Comparative Analysis of Plasma Protein Dynamics in Women with ST-Elevation Myocardial Infarction and Takotsubo Syndrome - Shafaat Hussain; Sandeep Jha; Evelin Berger; Linnea Molander; Valentyna Sevastianova; Zahra Sheybani; Aaron Shekka Espinosa; Ahmed Elmahdy; Amin Al-Awar; Yalda Kakaei; Mana Kalani; Ermir Zulfaj; et al. (Cells)
Background: ST-elevation myocardial infarction (STEMI) and Takotsubo syndrome (TS) are two distinct cardiac conditions that both result in sudden loss of cardiac dysfunction and that are difficult to distinguish clinically. This study compared plasma protein changes in 24 women with STEMI and 12 women with TS in the acute phase (days 0–3 post symptom onset) and the stabilization phase (days 7, 14, and 30) to examine the molecular differences between these conditions. Methods: Plasma proteins from STEMI and TS patients were extracted during the acute and stabilization phases and analyzed via quantitative proteomics. Differential expression and functional significance were assessed. Data are accessible on ProteomeXchange, ID PXD051367. Results: During the acute phase, STEMI patients showed higher levels of myocardial inflammation and tissue damage proteins compared to TS patients, along with reduced tissue repair and anti-inflammatory proteins. In the stabilization phase, STEMI patients exhibited ongoing inflammation and disrupted lipid metabolism. Notably, ADIPOQ was consistently downregulated in STEMI patients in both phases. When comparing the acute to the stabilization phase, STEMI patients showed increased inflammatory proteins and decreased structural proteins. Conversely, TS patients showed increased proteins involved in inflammation and the regulatory response to counter excessive inflammation. Consistent protein changes between the acute and stabilization phases in both conditions, such as SAA2, CRP, SAA1, LBP, FGL1, AGT, MAN1A1, APOA4, COMP, and PCOLCE, suggest shared underlying pathophysiological mechanisms. Conclusions: This study presents protein changes in women with STEMI or TS and identifies ADIPOQ, SAA2, CRP, SAA1, LBP, FGL1, AGT, MAN1A1, APOA4, COMP, and PCOLCE as candidates for further exploration in both therapeutic and diagnostic contexts.